A Pragmatic-Argumentative Reading of an Advertising Model - Boubaker, Fodil (El Omda in Linguistics and Discourse Analysis, 2020)
The publicity message is distinct discourse that combines language and image, so, because it aims to convince the recipient of the quality of the commodity, it employs a group of pilgrim mechanisms, and here, the pragmatic approach emerges as an effective approach in the detection of these mechanisms, therefore this study aims to clarify the way that the publicity discourse is made through the pragmatic and pilgrim approach for a publicity text.